The tadpole of Physalaemus fuscomaculatus (Anura: Leptodactylidae), with a description of internal oral morphology - Nomura, Fausto; Rossa-Feres, Denise De Cerqueira; Prado, Vitor Hugo Mendonça Do (Zootaxa, 2003)
The external morphology and internal oral features of Physalaemus fuscomaculatus (Steindachner, 1864) tadpoles are described and compared with other species in the Physalalemus biligonigerus group (Lynch, 1970). Tadpoles of P. fuscomaculatus have a morphology similar to other species within this group and closely resemble those of P. santafecinus Barrio, 1965 and P. biligonigerus (Cope, 1861). The tadpole of P. fuscomaculatus differs from those of the biligonigerus group by the following characters: i) proportionally shorter tail compared to total length, ii) presence of two narrow ventral gaps on marginal papillae of the oral disc; iii) upper jaw sheath Mshaped; iv) presence of two lingual papillae; v) two to three prepocket papillae, and vi) three to five pustulations anterior to each buccal pocket. This is the first record of Physalaemus fuscomaculatus in southeastern Brazil.